2015
DOI: 10.1111/1440-1630.12196
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a community of practice for Occupational Therapy curriculum development: The value of a two‐way process

Abstract: The commitment of time, planning and resources required to establish and participate in collaborative curriculum development with practice scholars is shown to be a valuable investment for occupational therapy academics, expert practice scholars and ultimately for student learning. Further studies of student and graduate outcomes from the curriculum are warranted. Potential future outcomes of this process include resilience in graduates and collaborative research with practice scholars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Including both low-level engagement (indirect and/or limited contact, including guest lectures and simulation assessments) and high-level engagement options (external advisory committee and co-design of curriculum or delivering curriculum modules) will be a key strategy for engaging clinicians and academics, from early career to senior professional experience groups [ 3 ]. Our findings resonated with previous studies that demonstrated an appetite for scholarly discussion and research amongst allied health professionals [ 14 , 41 , 42 ]. Building stronger links between learning, teaching, and research engagement options will be explored during future iterations of this collaborative project.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Including both low-level engagement (indirect and/or limited contact, including guest lectures and simulation assessments) and high-level engagement options (external advisory committee and co-design of curriculum or delivering curriculum modules) will be a key strategy for engaging clinicians and academics, from early career to senior professional experience groups [ 3 ]. Our findings resonated with previous studies that demonstrated an appetite for scholarly discussion and research amongst allied health professionals [ 14 , 41 , 42 ]. Building stronger links between learning, teaching, and research engagement options will be explored during future iterations of this collaborative project.…”
Section: Discussionsupporting
confidence: 90%
“…Practitioners’ insights ensure that health-professional graduates are prepared for the future workforce and realities of practice [ 13 , 14 ]. Thomas and Judd used a “community of practice” partnership between practice scholars and academic staff to review their occupational therapy curriculum and found that new graduates were potential “change agents with the profession” when their curriculum was developed in collaboration with practitioners [ 14 ] (p. 242). Garcia et al also found that a collaborative approach to curriculum development was essential for the sustainability of their new occupational therapy program [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curriculum content must also be developed through consultation with a range of stakeholders including consumers, carers and the occupational therapy practice community (Occupational Therapy Council (Australia & New Zealand)). Such consultation generally occurs between each occupational therapy program and occupational therapists practising in the local geographical area (Thomas & Judd, ). It is rare, however, to see this done at a more macroscopic, whole‐of‐profession, level.…”
Section: Introductionmentioning
confidence: 99%
“…The authors do not describe their learning community in any depth, but claim that including clinicians enabled them to bridge the gap between theory and practice (Boehm et al, 2015). Thomas and Judd (2015) similarly describe a community of practice (CoP) between practice scholars and academic staff. Their CoP met at three intervals over 18 months to develop a new occupational therapy program that reflected the realities of practice, at a university in Australia.…”
Section: Theme 3-collaborative Curriculum Developmentmentioning
confidence: 99%
“…Their CoP met at three intervals over 18 months to develop a new occupational therapy program that reflected the realities of practice, at a university in Australia. In their qualitative evaluation of participants' perceptions and experiences of participating in the CoP, there were specific benefits for curriculum development included developing a broad range of case studies that reflected the realities of practice and improved student fieldwork support (Thomas and Judd, 2015). In addition, therapists believed that new graduates had the potential to be change agents within the profession, would be able to develop roles in emerging areas of practice, and would be better prepared for the realities of practice.…”
Section: Theme 3-collaborative Curriculum Developmentmentioning
confidence: 99%